Estudos de avalanches de vórtices em filmes supercondutores de Nb e MgB2 - Colauto, Fabiano (2008)
If a type-II superconductor is cooled down in a zero applied field and subsequently an external field, larger than the first critical field, is applied, vortices enter through the sample borders until they are captured by pinning centers. As a consequence, the system achieves an inhomogeneous flux distribution, with a higher density of vortices near the border that progressively decreases toward the center of the sample. Under a small perturbation this self-organized state can lead to vortex avalanches that rush into the sample due to a thermomagnetic instability process. The motion of magnetic flux generates heat, which suppresses flux pinning and facilitates further flux motion. This provides a positive feedback mechanism that can result in a thermal runaway. The experimental study was accomplished through two techniques: bulk DC magnetometry and magneto-optical imaging. Under certain circumstances, avalanches develop as jumps in magnetization measurements and can also be seen in real time imaging. We have carried out a systematic study of the parameters involved in the occurrence of flux avalanches in superconducting thin films, submitted to perpendicular magnetic fields, a geometry which leads to dendritic profiles of flux penetration. The threshold values of field and temperature that encompass the region where avalanches to develop, as well as the instability boundary dependence on the film thickness, were identified. We have verified how an AC magnetic field influences on vortex avalanches and on the boundaries of instabilities. The study was also performed with an aluminum disk nearby the superconducting film, which suppresses vortex avalanches partially or totally, depending on the distance between film and disk, bringing the material to recover its capability of screening abrupt penetration of magnetic flux.